ANALISIS RASIO KEUANGAN TERHADAP RETURN SAHAM INDUSTRI REAL ESTATE AND PROPERTY DI BEI - Rosida Arumbinang, 08.05.51.0047; Sudiyatno, Bambang (Students Journal of Economic and Management, 2012)
This study aims to determine the effect of finance ratio DTA, ROE, PER, and EPS to the stock returns of Real Estate and Property company listed on the Indonesia Stock Exchange during the period 2005-2009. This research analyzed by multi regression analysis using SPSS program. The result showed that all variable significantly influence the stock returns.Key Words : return saham, Debt to Total Asset, Return on Equity, Price Earning Ratio, Earning per Share.